An Examination of the Disablement Process Among Older American Indians: The Native Elder Care Study - Schure, Marc B. (Gerontologist, 2016)
PURPOSE OF THE STUDY: Older American Indians disproportionately suffer from poorer physical and mental health and have greater disability compared to their racial and ethnic counterparts. The purpose of this study was to examine the disablement process among older American Indians. DESIGN AND METHODS: Data analyzed were from the Native Elder Care Study, which included in-person interviews with 505 community-dwelling American Indians aged ≥55 years. We used structural equation modeling to examine the contributive direct and indirect effects of health, demographic, and psychosocial risk factors on disability. RESULTS: Pathology had direct and indirect effects through social support and depressive symptoms on chronic pain intensity. Pathology also had direct and indirect effects on disability. Chronic pain intensity was a significant mediator between pathology and functional limitations. With contributive effects of older age and female sex, greater functional limitations were associated with increased disability. IMPLICATIONS: Our results support the theorized main pathway of the Disablement Process Model with our sample of older American Indians. Our findings support the importance of taking into account intra and extraindividual factors in assessing the prevalence and incidence of disability for older American Indians.